Prospect of Islamic Economic Studies - Syaeful Bahri (Enrichment : Journal of Management, 2021)
Various schools in economics such as capitalism, socialism and Islam, each have a history of development from day to day as well as advantages and disadvantages in their application. Islamic economics which is based on the Qur'an and Sunnah is considered by its adherents to be the most perfect system because it is based on divine law and does not only regulate the economy but also has a worship dimension. The development of Islamic economic studies, especially Islamic financial institutions in Indonesia in the last 5 years is very fast. Growth indicators can be seen from the growth of Islamic banking. The purpose of this paper is to find out the Prospects of Islamic Economic Studies. The source of this writing comes from books and other literature adapted. The development of Islamic studies in various elements of educational institutions encourages the development of Islamic economic studies. Which makes opportunities and challenges for the world of Islamic Economics to produce professional people so that they can run a system based on sharia, whether it is to fill educators in the Islamic economic education environment, writers of various Islamic economic literature or to become the driving force of the system of various Islamic financial institutions that are now is eager to spread its wings.